Living well with dementia: The role volunteer-based social recreational programs in promoting social connectedness of people with dementia and their caregivers. (3rd October 2022) - Sun, Winnie; Bartfay, Emma; Smye, Victoria; Biswas, Srija; Newton, Denyse; Pepin, Michelle; Ashtarieh, Bahar
Abstract: Objectives: This evaluation study was designed to examine the factors that contribute the promotion of social connectedness among people with dementia and their caregivers through social recreational programs; develop an understanding of volunteer's impact on program success; and identify the barriers and facilitators to improve the volunteer-based programs to promote social connectedness. Method: A qualitative descriptive research design was used to explore the study participants' lived experiences of social recreational programs from Alzheimer's Society of Durham Region (ASDR) in Ontario, Canada. A final sample of 31 participants was recruited including people with dementia, informal caregivers, and community volunteers. Qualitative data was collected through face-to-face semi-structured interviews. Emerging themes were derived from the qualitative descriptive data using thematic analysis. Results: The qualitative interviews highlighted the impact of social recreational programs on people with dementia, caregivers and volunteers in the promotion of social connectedness, as well as the examination of barriers and facilitators to identify opportunities for the future improvement of ASDR programs that would benefit the dementia populations. The study findings revealed that the project 'Living Well with Dementia' has been able to successfully foster social connectedness through its volunteer-led social recreational programs by promoting the physical and mental well-being of people with dementia and their caregivers. Conclusion: Our study findings underscored the critical roles of volunteers who contributed to the success of community-based programs. Future research is needed to identify the opportunities to address current gaps in services and to strengthen the social recreational programs using evidence-based practices and client-centered approaches. Supplemental data for this article can be accessed online at http://doi.org/10.1080/13607863.2021.1950614.